Performance and quality indicators and the governance process in Brazilian Federal Universities: a multi-case study - Lobato, Josiane de Oliveira; Andrade, Elida Furtado da Silva; Maccari, Emerson Antonio; Mazieri, Marcos Rogério (Revista de Administração da UFSM, 2019)
The aim of this study was to verify the relationship between the use of the performance and quality indicators and the governance process of the Brazilian federal universities. To achieve this, semi-structured script interviews were conducted with the managers of four universities with the best performance and quality indicators. Following the request to maintain anonymity in the interviews, universities were codified as University 1, University 2, University 3 and University 4. Secondary data were collected in bibliographical and documentary research on the official websites of the universities participating in the research. For the analysis of the results, the triangulation of data sources was used. As a result, it has been verified that governance has a great influence on the way in which management conducts its work, since management with greater maturity in the governance process better understand the importance of indicators and all institutional information, and use them in a strategic way.